Inventory Application with Average Perpetual System By using Visual Basic 2015 - Rahwani, Noor Romy; Nugraha, Gusti Nazar (INTEKNA informasi teknik dan niaga, 2016)
The purpose of this paper is to explain how to develop an inventory computer application using the average cost method determined by PSAK (Indonesian General Accepted Accounting Principles) No.14. This application is a windows based application developed by using Visual Basic 2015 and SQL Server 2014. The table relationship established for the application follows the rule of normalization called 3rd Normal Form. There were three steps that outline the research method employed by this paper i.e. analysing the current system, designing the recommended system, and applying the system design by developing the application.The company, called UD. Makmur, currently still adopted the last purchase approach to determine the cost of product sold to their customer. This approach is inappropriate according to the Indonesian GAAP No.14. There are two appropriate ways of valuing the inventory in accordance with the standard i.e. First in First out (FIFO) and Average Methods. Furthermore, the company had to count manually in order to know the inventory balance in a certain period.. This way is really inefficient and may also result physical riskÂ  By using the application developed through the research, the company can not only reduce both physical and financial risks, but also decrease the inefficiency in managing its inventory. Moreover, the inventory uses average method to inventory value, so the calculation has been compliance with the Indonesian GAAP (PSAK) No.14. Â